Development and internal validation of the Edmonton Obesity Staging System-2 Risk screening Tool (EOSS-2 Risk Tool) for weight-related health complications: a case-control study in a representative sample of Australian adults with overweight and obesity - Evan Atlantis; P Fahey; Kathryn Williams; Paul Dugdale; James Rufus John; SL Hocking; Kath Peters (BMJ Open)
Objective Excess weight and related health complications remain under diagnosed and poorly treated in general practice. We aimed to develop and validate a brief screening tool for determining the presence of unknown clinically significant weight-related health complications for potential application in general practice.Design We considered 14 self-reported candidate predictors of clinically significant weight-related health complications according to the Edmonton Obesity Staging System (EOSS score of ≥2) and developed models using multivariate logistic regression across training and test data sets. The final model was chosen based on the area under the receiver operating characteristic curve and the Hosmer-Lemeshow statistic; and validated using sensitivity, specificity and positive predictive value.Setting and participants We analysed cross-sectional data from the Australian Health Survey 2011–2013 sample aged between 18 and 65 years (n=7518) with at least overweight and obesity.Results An EOSS≥2 classification was present in 78% of the sample. Of 14 candidate risk factors, 6 (family history of diabetes, hypertension, high sugar in blood/urine, high cholesterol and self-reported bodily pain and disability) were automatically included based on definitional or obvious correlational criteria. Three variables were retained in the final multivariate model (age, self-assessed health and history of depression/anxiety). The EOSS-2 Risk Tool (index test) classified 89% of those at ‘extremely high risk’ (≥25 points), 67% of those at ‘very high risk’ (7–24 points) and 42% of those at ‘high risk’ (<7 points) of meeting diagnostic criteria for EOSS≥2 (reference).Conclusion The EOSS-2 Risk Tool is a simple, safe and accurate screening tool for diagnostic criteria for clinically significant weight-related complications for potential application in general practice. Research to determine the feasibility and applicability of the EOSS-2 Risk Tool for improving weight management approaches in general practice is warranted.